(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the current research is to identify the effectiveness of an (instructional -learning) design based on the dimensions of deep understanding in the acquisition of physical concepts by middle school students, to achieve the goal of the research, the research sample was randomly selected from Thawrat Al-Hussein Preparatory School for Boys, affiliated to the (General Directorate of Education in Baghdad, Al-Rusafa / Third), numbering (46) students divided into two groups, with (23) students in the experimental group who studied with the proposed instructional -learning design, and (23) ) students in the control group studied in the usual (followed) way, and the equivalence of the two groups was verified in the variables (chronological age in months, previous physical information, and intelligence). The researchers prepared the requirements of the experiment that included the proposed teaching-learning design (identifying the scientific material, defining physical concepts, formulating behavioral objectives, preparing teaching plans for the experimental and control groups, and preparing learning activities) the physical concepts acquisition test consisting of (27) objective paragraphs of a multiple-choice type with four alternatives was also built. Its psychometric properties were confirmed. The two groups were studied by the third researcher, and after the end of teaching the scientific material, the research tool was applied, and the results were analyzed using the (t-test) equation for two independent samples. The results showed that there was a statistically significant difference at the level of significance (0.05) in favor of the experimental group over the control group in the physical concepts acquisition test, with a large effect size.